Apollonius Dyscolus' Treatise On the Pronoun or On Pronouns? Troubles with the Text's Transmission. - Dumarty, Lionel (Classical Philology, 2025)
Three treatises have survived from the work of the grammarian Apollonius Dyscolus (second century CE) on the study of the parts of speech: one on pronouns, one on adverbs, and one on conjunctions. The aim of this article is to take stock of one particular aspect of the manuscript tradition in this corpus that is as intriguing as it is marginal: in the sole surviving manuscript, two of these three treatises are entitled in the plural—Περὶ ἐπιρρημάτων (On Adverbs) and Περὶ συνδέσμων (On Conjunctions)—while the third is in the singular: Περὶ ἀντωνυμίας (On the Pronoun). The first aim of our investigation is to explain this strange disparity and outline the reasons why it has become so widespread in Apollonian studies. On this basis, in view to re-editing the treatise On the Pronoun , it will be necessary to decide whether to maintain the singular form or to use a plural form, as in the case of the other two.